Kendala-Kendala yang Menyebabkan Pria Kaum Bapa Tidak Aktif Beribadah - Setiawan Majusip; Jeane Marie Tulung; Olivia Cherly Wuwung (Peneliti.net, 2021)
This study aimed to find out the elders roles of the men’s ministry in the worship inactivity at Chistian Evangelical Church in Talaud ( Germita) congregation of Sanggoloma in Moronge, to identify the obstacles influenced by the elders duties of the men's ministry in the congregation, and also to analyze the efforts done by the men's ministry to overcome the problem. Data were collected through observation, documentation, and relevant literature studies. The method used was qualitative research. The result of this study was that in the men's ministry, the elders had an essential role for faith development in increasing worship voluntary. Therefore, the men's ministry should maximize their services by inclining communication and cooperation in serving, increasing consistency on Bible teachings when performing services, be creative in motivating and increasing the men's ministry awareness of their church calling especially in worship voluntary, be more creative and sensitive in determining the time of worship, be patient and ask God for wisdom in carrying out the service and keep praying for the ministry.